Possibilities of Organization of Education Based on Mobile and Information Technologies - Zhurayev Ilkhom Iskhokovich (Genius Journals, 2025)
This study analyzes the role of mobile applications in teaching subjects, their impact on students, and the innovative approaches they bring to the educational process. The study examined interactive forms of learning based on mobile technologies, mobile platforms for learning programming, and their effectiveness.
Keywords: mobile educational technologies; learning programming; educational innovations